Prevalence and correlates of alcohol dependence in an Australian Aboriginal and Torres Strait Islander representative sample: Using the Grog Survey App. (25th April 2021) - Weatherall, Teagan J.; Conigrave, James H.; Conigrave, Katherine M.; Perry, Jimmy; Wilson, Scott; Room, Robin; Fitts, Michelle S.; Hayman, Noel; Lee, K. S. Kylie
Abstract: Introduction: Little is known about the prevalence of current alcohol dependence in Indigenous Australian communities. Here we identify the frequency of reported symptoms, estimate the prevalence and describe the correlates of current alcohol dependence. Methods: A representative sample of Indigenous Australians (16+ years) was recruited from an urban and remote community in South Australia. Data were collected between July and October 2019 via a tablet computer‐based application. Participants were likely dependent if they reported two or more dependence symptoms (ICD‐11; in the last 12 ‐months), weekly or more frequently. Chi‐square tests described the relationship between demographics, remoteness and alcohol dependence. Spearman correlations estimated the relationship between symptoms of dependence, consumption characteristics and demographics. Results: A total of 775 Indigenous Australians participated. The most frequently reported symptoms were prioritising alcohol over other things and loss of control. Overall, 2.2% were likely dependent on alcohol ( n  = 17/775). Prevalence did not vary by remoteness. Participants who drank more and more frequently tended to report more frequent symptoms of dependence. In the urban site, men tended to report more frequent symptoms of dependence than women. Age, income and schooling were not linked to dependence. Discussion and Conclusions: The prevalence of current alcohol dependence in this representative sample was similar to that of the general Australian and international estimates. Understanding risk factors for current alcohol dependence will be useful to inform the allocation of funding and support. Accurate estimates of the prevalence of current alcohol dependence are important to better identify specialist treatment needs.